Identification of 2 Novel Species, Mycobacterium novusgordonae and M. shingordonae - Kazuki Hashimoto; Yuko Abe; Kiyoharu Fukushima; Yuki Matsumoto; Haruko Saito; Yuri Akamine; Takayuki Niitsu; June Yamauchi; Tadayoshi Nitta; Michio Tanaka; Takuro Nii; Takanori Matsuki; et al. (Emerging Infectious Diseases, 2025)
We identified 2 novel species, Mycobacterium novusgordonae and M. shingordonae, from sputum specimens of pulmonary disease patients in Japan. Genetic and biochemical analyses revealed a close relationship with M. paragordonae. One M. shingordonae case-patient experienced severe progressive infection, highlighting the variation in pathogenicity of the M. gordonae clade species.